Brazilian culture from Teletandem interactants’ point of view - Brocco, Aline de Souza; Baptista, Janara Barbosa (The ESPecialist, 2014)
The purpose of this paper is to investigate how two Brazilian interactants build their culture to two foreign interactants in a teletandem context, as this environment is considered propitious to the exchange of cultural aspects. The analyzed data indicated that there were comparisons between cultures, generalizations, and stereotype constructions due to the individualization of the culture from the Brazilians’ point of view. One of the analyzed pairs presented a larger exchange of cultural information probably due to level of proficiency, integration, individual characteristics and interest.